INDONESIA IS COMBATING CORRUPTION: A Struggle between the Extra-Ordinary Measurement and Extraordinary People - Heniarti, Dini Dewi (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2016)
Currently, the practices of mafia of law in Indonesia is getting more rampant. Law enforcement is very slow, many cases of corruption offenses as crimes extra ordinary crime are addressed will slow grind lower law. Ineffective of law in Indonesia is also dependent on these factors. Primarily extraordinary people. Several law enforcement officials are easily bribed by corrupt actors with the aim to escape punishment, or lighten their sentences. Laws are formulated to deal with corruption seem barren. Factually Indonesia show that is still ranked below Malaysia, Singapore, and Hong Kong, as well as Vietnam and the Philippines. Outcome in the form of impacts and benefits of combating corruption unclear to this day. This paper will to describe that law enforcement combating corruption will be support by extra ordinary measure and extra ordinary people. Especially, Indonesia, a majority Muslim country in fact the largest Muslim country in the world, a large number of Islam is really potential become a leader in the combating corruption.***Praktek mafia hukum di Indonesia saat ini lebih merajalela. Penegakan hukum saat ini sangat lambat, banyak kasus tindak pidana korupsi sebagai kejahatan extra ordinary ditangani lambat laun akan menggiring hukum yang lebih rendah. Tidak efektifnya hukum di Indonesia tergantung juga pada faktor-faktor ini: pejabat penegak hukum yang mudah disuap oleh pelaku korupsi dengan tujuan untuk menghindari hukuman, atau meringankan hukuman mereka; hukum yang diformulasikan untuk menangani korupsi tampaknya mandul. Secara faktual Indonesia masih berada di bawah peringkat Malaysia, Singapura, dan Hong Kong, serta Vietnam dan Filipina dalam hal penanganan korupsi. Tulisan ini akan menjelaskan bahwa penegakan hukum dalam pemberantasan korupsi membutuhkan dukungan dengan tindakan luar biasa dan orang luar biasa. Terutama Indonesia, yang mayoritas penduduknya Muslim benar-benar potensial bagi kelahiran pemimpin yang mampu memerangi korupsi.